ANALISIS YURIDIS KEWENANGAN KESATUAN PENJAGAAN LAUT DAN PANTAI DALAM PENINDAKAN PELANGGARAN HAK LINTAS DAMAI PELAYARAN DI PERAIRAN INDONESIA - Mariana Zhuo; Jemmy Rumengan; Henry Aspan (MIZAN, Jurnal Ilmu Hukum, 2020)
Each country basically has the right to sail in its territorial sea, exclusive economic zone, open sea, and territorial sea belonging to other countries. But in this case relating to the right to sail at sea or territorial waters belonging to other countries, Subject to the provisions of the 1982 Sea Law Convention II, ships of all countries, both coastal and non-coastal countries, enjoy the right of peaceful crossing through territorial seas. The problem in this study is how the legal arrangement of the authority of the sea and coast guard unit in the enforcement of violations of the right to cross the peace in Indonesian waters ,. The conclusion of this study Law enforcement at sea is still sectoral because many government agencies are authorized at sea with various legal bases at their disposal and have the potential to cause many legal problems, including overlapping authority between law enforcement agencies which causes conflicts between law enforcement agencies so optimize the interagency sector that exists in the supervision and protection of jurisdictions in the waters, and strict sanctions must be held against violations of the right to peace in the path of the rights to peace in Indonesia Keywords: Authority, Sea and Coast Guard Unit, Right of Peace ABSTRAK Setiap negara pada dasarnya memiliki hak untuk berlayar di laut teritorialnya, Zona ekonomi eksklusif, laut lepas, dan laut territorial milik negara lain. Namun dalam hal ini berhubungan dengan hak untuk berlayar di laut atau perairan teritorial milik Negara lain, Dengan tunduk pada ketentuan Konvensi Hukum Laut II Tahun 1982 , kapal semua negara, baik negara berpantai ataupun negara tak berpantai, menikmati hak lintas damai melalui laut teritorial. Permasalahan dalam penelitian ini adalah bagaimana pengaturan hukum kewenangan kesatuan penjagaan laut dan pantai dalam penindakan pelanggaran hak lintas damai di perairan indonesia,. Kesimpulan dari penelitian ini Penindakan hukum di laut masih bersifat sektoral karena banyak instansi pemerintah yang berwenang di laut dengan berbagai dasar hukum yang dimilikinya dan berpotensi menimbulkan banyak permasalahan hukum, di antaranya tumpang tindih wewenang antar instansi penegak hukum yang menimbulkan konflik antar lembaga penegak hukum sehingga perlu mengoptimalkan sektor antar lembaga yang ada dalam pengawasan dan perlindungan wilayah hukum di perairan, serta perlu diadakan sanksi yang tegas terhadap pelangaran hak lintas damai di jalur hak lintas damai di perairan indonesia Kata Kunci: Kewenangan, Kesatuan Penjagaan Laut dan Pantai, Hak Lintas Damai